KAJIAN PERUBAHAN FISIK RUMAH TINGGAL PADA EKS UNIT PERMUKIMAN TRANSMIGRASI KAMPUNG WARBO, PAPUA - Hasrul Hasrul; Inayatul Ilah Nashruddin (DINAMIS, 2015)
Keerom regency is one of 217 area which is ex- Transmigration residence in Papua, that is developed to be an independent district and support the development others areas. Warbo is one of ex-transmigration village which in 1990 began settled by majority of java tribes, Nusa Tenggara Timur tribes, and Sulawesi Selatan tribes. The warbo village is quickly developed because it is located near with Abepura city. This in the reason why many people want to continue to live in there. The development is mostly shown by their house which almost chage entire their construction around main road. This difference is caused by several factors. The purpose of this review is to know about the changing of the ex-transmigration’s residence of their house physical shape and what kind of the factors influenced it. The methodology of the research is descriptive method and explanatory approachment. The approachment is used to identify what kind of changing that happened from; the function and how many rooms, structure changing, the change of building envelope, and what factors are influenced that changing. The result of this study is know that the change happened because the changing of the house ground plane with add several rooms, changing of building structural, and chaging of building envelope. The factors that influenced of the changing are: (1) the basic needs of the house which than increase become the demand getting the comfortable house; (2) the response of the environment condition, especially climate and antivipate of the flooding; (3) amount of the families members which it becomes the primary factor og the changing of the house physic shape that usually done by add the room or change the room’s function,; (4) the activities of the house members, it is also another factor that influenced the changing of the house physic shape. This is shown through the adding of room which it is function as the provider of activities done before, and (5) the last one is social factor.